Towards Practical C++ Programming Projects for Pre-University Engineering Students - Motalebi, Foad (Asian Journal of Computer and Information Systems, 2013)
One of the key assessments for C++ programming is the programming project. These programming projects encourage Project Based Learning. Creating and designing a programming project for novice programmers can be a challenging task. This can be compounded by the fact that students may find the project difficult to do and loose interest in the process. So it is befitting to create and design project topics which are practical and interesting and are perceived as such by students. This would encourage students to see the relevance of coding in the real world outside the class and generate exuberance in the programming project. The main motivation of this paper is to show the various C++ projects given to engineering pre-university students over a period of 3 years at Curtin University, Sarawak and in doing so to observe their inclination towards practical project. A project’s inclination towards practicality and the interest it generated is done by analysing student performance in their programming project for every semester.